The Implementation of Technology-Assisted Learning in EFL Instruciton: A Qualitative Study in an EFL Classroom in West Nusa Tenggara - Narayana, I Gede Perdana Putra; Yahya Himni, M Saleh (INGGARA (Jurnal Pendidikan Bahasa Inggris dan Bahasa Arab), 2024)
The use of technology in the teaching of English as a Foreign Language (EFL) has caught the interest of researchers, educators, and governments all around the world. Technology's quick development has created chances for innovative and fun learning experiences. An increasing number of people in the Indonesian province of West Nusa Tenggara are eager to use technology-assisted learning techniques to enhance EFL instruction in local institutions. The purpose of this qualitative study is to examine how technology-assisted learning is used in a West Nusa Tenggara EFL classroom from the viewpoint of the instructors. This study aims to get a thorough understanding of teachers' experiences, opinions, and instructional practices linked to the integration of technology in EFL education through the use of qualitative research methodologies like document analysis and interviews. The outcomes show how theories of technology-assisted language acquisition are really put into practice in the classroom. The teacher efficiently uses a variety of digital tools, appreciates their benefits, and effectively deals with challenges by putting methods into place to get through them. The students' positive feedback and the school's supply of technology resources show a dedication to upholding the tenets of technology-assisted language learning. The integration of technology is also reflected in the instructional plan. However, a more thorough analysis of how technology affects pupils' language proficiency may be a potential for future research.